Case-control study of maternal and fetal outcomes in beta thalassaemia trait during pregnancy. - Shyamali Thilakarathne; Udayanga P Jayaweera; Sanjaya Uduweralla; Sudath Pathinisekara; Thushari U Herath; Anuja Premawardhena (PLoS ONE)
Individuals with beta thalassaemia trait are not expected to have clinically significant morbidities besides mild anaemia. Pregnancy would exaggerate the anaemia in beta thalassaemia traits, but how this could affect maternal and fetal outcomes is unclear. Previous studies on maternal and fetal outcomes in beta thalassaemia trait have been inconsistent and even contradictory. Thus, we aimed to study the outcomes of pregnancy in pregnant women with beta-thalassemia trait. The prospective case-control study included 120 pregnant women with beta thalassaemia trait and 120 normal pregnant women. Participants in the case and control groups were matched according to maternal age, gestational age and number of previous pregnancies. All participants were followed up at similar intervals for the duration of the pregnancy for haemoglobin variations, transfusion requirements and maternal/fetal problems without interfering with the management. We identified that beta thalassaemia traits did not experience noteworthy symptoms in any of the three trimesters: except for headache. Haemoglobin level, and red cell indices in all three trimesters were significantly lower among cases than controls. In both groups hemoglobin levels dipped in the 2nd trimester, only to rise in the 3rd trimester, to reach values similar to those in the 1st trimester. Individuals with beta thalassaemia trait were transfused more blood during the 2nd and 3rd trimesters based on lower Hb levels of the mother a decision not prompted by any notable maternal or fetal complications. No statistically significant differences were observed for pregnancy complications, perinatal or neonatal outcomes. During labor, the rate of caesarean deliveries was significantly higher among cases with no definite indications for such in most cases.